2019
DOI: 10.1002/wps.20671
|View full text |Cite
|
Sign up to set email alerts
|

The effect of minority status and social context on the development of depression and anxiety: a longitudinal study of Puerto Rican descent youth

Abstract: Few longitudinal studies have explored to date whether minority status in disadvantaged neighborhoods conveys risk for negative mental health outcomes, and the mechanisms possibly leading to such risk. We investigated how minority status influences four developmental mental health outcomes in an ethnically homogeneous sample of Puerto Rican youth. We tested models of risk for major depressive disorder (MDD) and generalized anxiety disorder (GAD), depressive and anxiety symptoms (DAS), and psychological distres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
64
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 85 publications
1
64
1
Order By: Relevance
“…However, the prevalence among BYS young men from PR (8.2%) was almost five times higher. 30 Among adults, two studies conducted in the 1990s 53,54 agreed with the National Latino and Asian American Study, conducted 17 years ago, which also showed women having a higher prevalence of lifetime (19.8%) and past-year (10.8%) MDD than men (10.9% and 6.4%, respectively). 55 In the BYS, prevalence of lifetime MDD was 15.0% for men from SBx and 13.3% for men from PR.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…However, the prevalence among BYS young men from PR (8.2%) was almost five times higher. 30 Among adults, two studies conducted in the 1990s 53,54 agreed with the National Latino and Asian American Study, conducted 17 years ago, which also showed women having a higher prevalence of lifetime (19.8%) and past-year (10.8%) MDD than men (10.9% and 6.4%, respectively). 55 In the BYS, prevalence of lifetime MDD was 15.0% for men from SBx and 13.3% for men from PR.…”
Section: Discussionsupporting
confidence: 60%
“…A recent BYS article focused on MDD and anxiety disorders in young adulthood points to the relevance of sociocultural processes for understanding the early development of psychopathology among youths. 30 Earlier BYS work focused on childhood and early adolescence, together with existing literature, identified the importance of sociocultural risk and protective factors. For example, higher parental acculturation and experiences of discrimination and cultural stress in children have been related to greater symptoms and poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of suicidal ideation found in our sample is quite impressive, compared with the 3% found in a previous epidemiological study carried out in Italy [98]. Several factors may contribute to the increased rate of suicidal ideation in the Italian general population, including uncertainty about the future, loneliness, physical distancing, unemployment, economic recession and interpersonal violence [99]. All these risk factors should be taken into account in the implementation of actions aiming to prevent suicide [100][101][102].…”
Section: Discussionmentioning
confidence: 47%
“…Youths in SBx, however, growing up as part of an ethnic minority group, are likely to face ethnic discrimination throughout life, an experience likely related to psychopathology. 14,15 Rates of people living with human immunodeficiency virus/acquired immunodeficiency syndrome were 10 times higher than the U.S. average in SBx in 2017, 16 5 times more than the total PR population and over 2 times higher than the population in San Juan, PR. [16][17][18] Rates of sexually transmitted infections in SBx ranged from 3 to 7 times higher than the rates for people living in PR in 2016.…”
mentioning
confidence: 99%